Effect of Reaction Temperature on Adhesive Properties of Waterborne Polyurethane/Acrylic Hybrids Synthesized by Semicontinuous Miniemulsion Polymerization. Issue 10 (25th July 2013) - Ballard, Nicholas; Carretero, Paula; Asua, José M.; Izadi, Hadi; Penlidis, Alexander
Abstract Hybrid polyurethane/acrylic particles have been synthesized by miniemulsion polymerization at various temperatures to determine the effect of the reaction temperature on the polymer microstructure and the adhesive properties of films prepared from latexes. Simultaneous free radical polymerization of a mixture of (meth)acrylic monomers in the presence of 2‐hydroxyethyl methacrylate and addition polymerization of an isocyanate terminated prepolymer and chain extending diol have been performed and the resulting polymers are characterized in terms of their gel content, sol molecular weight, swelling degree, and microgel size. The changes in the polymer microstructure are related to bulk effects in the adhesive films resulting from differences in the polymerization kinetics at different temperatures.<inline-graphic xlink:href="ark:/27927/pgg3ss061vg" content-type="mren201300122-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />